2017
DOI: 10.1097/md.0000000000009139
|View full text |Cite
|
Sign up to set email alerts
|

Collision tumors composed of meningioma and growth hormone-secreting pituitary adenoma in the sellar region

Abstract: Rationale:Collision tumor is a rare disease that represents the coexistence of two histologically distinct neoplasms in the same area without histological admixture or an intermediate cell population zone. To our best knowledge, 13 cases besides our 2 cases have been reported till now, and our report represents the first publication regarding a collision tumor composed of growth hormone (GH)-secreting pituitary adenoma and sellar meningioma.Patient concerns:We collected two cases of collision tumors composed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…A preference for parasellar localization was found with 22 cases, [4][5][6]10,13,14,16,22,[25][26][27]29,31,[33][34][35][36][38][39][40] of which in 13 cases the tumours were contigious. 6,10,14,22,26,27,31,33,35,[38][39][40] In only three a distinction had been made between the tumours preoperatively. 26,27,32 When a meningioma or a pituitary adenoma becomes symptomatic and a MRI is made it is possible that an incidental meningioma or pituitary adenoma is seen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A preference for parasellar localization was found with 22 cases, [4][5][6]10,13,14,16,22,[25][26][27]29,31,[33][34][35][36][38][39][40] of which in 13 cases the tumours were contigious. 6,10,14,22,26,27,31,33,35,[38][39][40] In only three a distinction had been made between the tumours preoperatively. 26,27,32 When a meningioma or a pituitary adenoma becomes symptomatic and a MRI is made it is possible that an incidental meningioma or pituitary adenoma is seen.…”
Section: Discussionmentioning
confidence: 99%
“…However, 5 of the 10 cases occurred in the last five years. 22,26,35,40 Our literature review will be an underrepresentation of the real prevalence. During a retrospective study concerning pituitary adenomas seven other patients were found that were diagnosed with a pituitary adenoma and a concomitant meningioma in our hospital during the last seven years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of 548 transsphenoidally resected pituitary adenomas, collision tumors accounted for 1.46% [5]. Collision tumors containing pituitary adenoma-sellar meningioma have been described in only four cases to date [6][7][8]. As the fifth case, we present a case harboring a collision tumor comprising a pituitary corticotroph adenoma and a sellar meningioma in the same anatomic position.…”
Section: Introductionmentioning
confidence: 83%
“…The presence of a lung lesion could also represent a second primary; however, microscopic and immunohistochemical findings did not support a lung origin. Meningioma may also be a consideration as part of a sellar collision tumor with pituitary adenoma [19,37], and a clear cell meningioma may resemble clear cell renal cell [38,39]; however, recent studies have reported VHL inactivation alone is insufficient to cause tumor formation [40]. We do not have germ cell data to ascertain if our patient had VHL disease; however, the presence of VHL and NOTCH2 in both tissue samples and the history or renal clear cell carcinoma suggest an abnormality that points towards germ-line mutation.…”
Section: Discussionmentioning
confidence: 99%